Sustainable Transport Practices in Shipping Managing Emissions and Reducing Environmental Impact - Rafid Zayan; Tawhid Farhan Alam (Shipping and Transport Management Journal, 2025)
The shipping industry plays a crucial role in global trade, but it also significantly contributes to environmental degradation, particularly through emissions and fuel consumption. This research aims to explore sustainable transport practices in the shipping sector, focusing on the management of emissions and efforts to reduce environmental impacts. A combination of qualitative and quantitative methods was used to analyze existing literature, case studies, and data from shipping companies implementing sustainable practices. The findings highlight the potential of alternative fuels, emission-reducing technologies, and operational efficiency improvements in mitigating the sector's environmental footprint. Additionally, the research explores the regulatory frameworks and incentives that drive sustainability in shipping. The study underscores the importance of collaboration among industry stakeholders and policymakers to achieve long-term environmental goals. The implications of the findings provide valuable insights for shipping companies, environmental advocates, and policymakers aiming to advance sustainability in maritime transport.